2002
DOI: 10.1002/ajmg.b.10024
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of attention problems in children: I. cross‐sectional results from a study of twins, age 3–12 years

Abstract: Multiple twin studies of attention problems (AP) from the Child Behavior Checklist or ADHD from the DSM criteria have reported on the genetic and environmental influences on these behaviors. The majority of these have studied AP and ADHD symptoms in twin samples combined across wide age spans, combined rater information and both genders. Thus, it is possible that the results are complicated by developmental, informant, and gender differences. The purpose of this study was to assess for the genetic and environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
88
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 44 publications
11
88
0
2
Order By: Relevance
“…If these contrast effects are not accounted for in the analysis, mother ratings will result in lower DZ concordance rates and successively in an overestimation of heritability. Rater contrast effects were described for the Rutter-A scale, the DBRS, parental interview data obtained by the CAPA (Table 1) and for the CBCL at age 3 only but not for children aged 7-12 years old [47,89,90].…”
Section: Rater Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…If these contrast effects are not accounted for in the analysis, mother ratings will result in lower DZ concordance rates and successively in an overestimation of heritability. Rater contrast effects were described for the Rutter-A scale, the DBRS, parental interview data obtained by the CAPA (Table 1) and for the CBCL at age 3 only but not for children aged 7-12 years old [47,89,90].…”
Section: Rater Effectsmentioning
confidence: 99%
“…If MZ variance is smaller than DZ variance, and DZ correlation is very low compared to MZ correlation, this is indicative of a rater contrast effect. Structural equation models allow differentiating between dominant genetic and rater effects [89,91]. Heritability in the broad sense refers to additive and dominant genetic effects together; heritability in the narrow sense refers only to additive genetic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Male and female data were combined in the MZ twin, DZ twin, and twin-sibling groups in the genetic analyses because there is no evidence for sex differences in heritability for ADHD (Derks et al, 2004;Derks et al, 2007;Hudziak et al, 2005;Rietveld et al, 2003) and IQ (Bartels, Rietveld, van Baal & Boomsma, 2002), and the power to detect sex differences in genetic influences in the independent samples was limited (Polderman, Stins, et al, 2006). MZ twins share all their genes whereas DZ twins and siblings share on average half of their segregating genes.…”
Section: Genetic Analysesmentioning
confidence: 99%
“…and Rietveld et al (2003) demonstrated that genetic influences on AP are equally important for boys and girls. AP are often assessed with behavior questionnaires that can be completed by different informants.…”
mentioning
confidence: 99%
“…Studies in children, however, have had to rely on informants who rate the behavior of both twins. In this design, non-additive genetic influences are difficult to distinguish from rater contrast effect, in which an informant magnifies differences in DZ twins to a larger extent than in MZ twins (Rietveld et al 2003). Many studies of infants and toddlers show heritability estimates for extraversion and its correlates from approximately 35-47% across twin and adoption designs (Dilalla and Jones 2000).…”
Section: Introductionmentioning
confidence: 99%